2019
DOI: 10.3390/cli7040052
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Relationships between Drought Indices and Wildfire Danger Outputs: A Test Case for the California-Nevada Drought Early Warning System

Abstract: Relationships between drought indices and fire danger outputs are examined to (1) incorporate fire risk information into the National Integrated Drought Information System California–Nevada Drought Early Warning System and (2) provide a baseline analysis for application of drought indices into a fire risk management framework. We analyzed four drought indices that incorporate precipitation and evaporative demand (E0) and three fire indices that reflect fuel moisture and potential fire intensity. Seasonally ave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…and destructive wildfires both historically and recently (McEvoy et al, 2019). These regions also provide surface water to large populations and/or major regional agricultural areas, making them ideal for studying long-term hydrologic drought.…”
Section: 1029/2020ef001736mentioning
confidence: 99%
See 3 more Smart Citations
“…and destructive wildfires both historically and recently (McEvoy et al, 2019). These regions also provide surface water to large populations and/or major regional agricultural areas, making them ideal for studying long-term hydrologic drought.…”
Section: 1029/2020ef001736mentioning
confidence: 99%
“…Evaporative demand ( E 0 )—the upper limit of actual evapotranspiration ( ET ) that could occur given unlimited surface water supply (Hobbins et al, 2017)—has a strong connection to drought and wildfire potential in the western United States (e.g., Abatzoglou & Kolden, 2013; Abatzoglou & Williams, 2016; Littell et al, 2016; McEvoy et al, 2016) and globally (e.g., Dai, 2011; Vicente‐Serrano et al, 2010). In California and Nevada, elevated E 0 contributed to the 2012–2016 drought's severity (Hobbins et al, 2016; McEvoy et al, 2016; Shukla et al, 2015; Williams et al, 2015) and to wildfire potential (Brown et al, 2020; McEvoy et al, 2019; Nauslar et al, 2019). Although E 0 is sometimes calculated from temperature alone, a physically based E 0 formulation is critical to obtaining realistic estimates that include not only temperature changes but also the wind speed, humidity, and incoming shortwave radiation components that drive land surface‐atmosphere interactions and drying (Hidalgo et al, 2005; Hobbins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that wildfires occur more frequently and become more severe in hot and dry weather [7]. Thus, heat and drought indices have served as a proxy for predicting the intensity and frequency of wildfires [8][9][10]. However, accurately predicting wildfires is still difficult.…”
Section: Introductionmentioning
confidence: 99%